Effect of thyroid hormone on cardiac function following orthotopic heart transplantation in piglets. (14th July 2017) - Kumar, T. K. Susheel; Mathis, Craig; Sathanandam, Shyam; Zurakowski, David; Subramanian, Saradha; Allen, Jerry; Solimine, Michael; Berrios, Lindsay; Jackson, Scott; Landers, Mark; Sullivan, Ryan; Barnett, Stacey; et al.
Abstract: Studies in adult HT have demonstrated improved cardiac function in the recipient following administration of T3 to the donor. The purpose of this experiment was to assess the effects of T3 on the function of the immature donor heart following HT in a piglet model. A total of 32 piglets were divided into 16 donors and 16 recipients. Following creation of brain death, half of the donor piglets were randomized to receive three doses of T3 (0.2 μg/kg) along with hydrocortisone (1 mg/kg). The donor hearts were then transplanted into the recipient piglets on CPB. Duration of survival off CPB, inotrope score, and EF of heart following CPB were evaluated. There were no differences between the two groups in age, weight, pre‐brain death EF, T3 levels, and CPB times. Post‐CPB survival times were inversely related to the ischemic times in both groups (Pearson r=− 0.80, P <.001), and this relationship was not influenced by T3. There was no difference in inotrope score, EF, or biochemical assessment between the two groups. Administration of T3 in combination with hydrocortisone to the brain‐dead donor confers no beneficial effect on myocardial function or survival following HT in a piglet model.